2023
DOI: 10.3389/fnut.2023.1109824
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes is associated with loss of appendicular skeletal muscle mass and sarcopenia

Abstract: BackgroundDecreasing mass and metabolism in skeletal muscle are associated with increasing insulin resistance (IR) and type 2 diabetes mellitus (T2DM). The causal relation between sarcopenia and abnormal glucose metabolism may be bidirectional. This investigation is aimed to explore the detailed correlation between pre-diabetes and sarcopenia in United States (US) adults.MethodsA total of 22,482 adults aged ≥20 years in the National Health and Nutrition Examination Survey (NHANES) were included. Generalized li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…The role of gender, on the other hand, remains unclear in the literature. While in the cohort of this study, a relationship between LM and glycemic control was only obtained in women, there are other studies in which this relationship between T2D and SMM only appears in men [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The role of gender, on the other hand, remains unclear in the literature. While in the cohort of this study, a relationship between LM and glycemic control was only obtained in women, there are other studies in which this relationship between T2D and SMM only appears in men [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 64%
“…According to a recent meta-analysis, three studies that used body mass index, SMI, or appendicular skeletal muscle mass as measures of muscle mass showed that poor glycemic control was strongly associated with loss of muscle mass but not with loss of muscle function [ 41 ]. It is known that each 10% increase in SMI is associated with a 12% reduction in prediabetes or established diabetes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that there is an association between prediabetes and reduced appendicular muscle strength [ 89 , 90 ]. The diminished muscle strength is attributed to insulin resistance, elevated inflammatory cytokines, and advanced glycosylation end products (AGEs) associated with prediabetes and type 2 diabetes [ 91 , 92 ].…”
Section: Prediabetesmentioning
confidence: 99%
“…There is an onset of reduced skeletal muscle strength of lower extremities, with hand grip strength being the least affected. Complications are noted over PreDM progression [ 89 , 90 , 94 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation